KONSEP UMMAH WĀHIDAH DALAM AL-QUR’AN DAN RELEVANSINYA DENGAN KONTEKS KEKINIAN: Studi Komparatif Penafsiran Hamka dan Kementerian Agama RI - Nurmansyah, Ihsan; Oktaviana, Sherli Kurnia; Annisa, Nur (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
Basically Muslims around the world are ummah wahidah. But in reality, some Muslims actually conflict with each other and are divided due to differences in opinions, views, by blaming each other and disbelief. Therefore, how do the concepts of the two interpretations written by Hamka and the Ministry of Religion RI respond to this problem, where the two interpretations discuss about society. The method used is the comparative method. The results of this study are 1) Hamka and the Ministry of Religion RI agree in interpreting ummah wahidah as one belief in monotheism and one who likes to do good. Both of them provide a way to realize ummah wahidah by returning to the book that contains the truth and mentioning the factors that become obstacles to the realization of ummah wahidah, namely envy. The difference is, in explaining the meaning, constraints and ways of realizing ummah wahidah, Hamka is more detailed, while the Ministry of Religion RI is simpler; 2) The ummah wahidah offered by Hamka and Ministry of Religion RI is still very relevant to the current context. From the two books of his commentary, he provides a solution so that Muslims adhere to the Al-Quran and as-Sunnah. Meanwhile, Hamka specifically provides a way for humans to return to their unity by finding common ground that refers to good values, even as a means to compete in goodness; 3) The implication is that Muslims must change their mindset and be mature to accept the differences that exist.